Changes in Aroma Profile of Shiitake Mushroom (Lentinus edodes) during Different Stages of Hot Air Drying - Qin, Lei (Foods, 2020)
To clarify the changes in the aroma characteristics of shiitake mushrooms (Lentinus edodes) during hot-air drying, volatile compounds of L. edodes were analyzed using sensory evaluation, electronic nose, and purge and trap combined with gas chromatography-mass spectrometry (PT-GC-MS) at different timepoints of the drying process. Results showed that the sensory and volatile profile changed significantly during the drying process at 60 °C for up to 12 h and the drying process could be divided into three stages: early stage (<2 h), middle stage (2–3.5 h) and late stage (>3.5 h). Volatile compounds in fresh L. edodes consisted mainly of ketones and alcohols. The early stage of drying decreased the concentration of ketone and alcohol compounds and promoted the generation of cyclic organosulfur compounds through a series of enzymatic and non-enzymatic reactions, which mainly contribute to the characteristic odor of shiitake mushroom. Partial least squares-discriminant analysis (PLS-DA) showed that the volatile compounds released after different drying times could be divided into four groups, which have been confirmed by sensory evaluation results. The results suggested that the unique flavor of dried mushrooms is mainly due to the activation of enzymes during the drying process, which act on lentinic acid to produce sulfur-containing heterocyclic compounds. We believe that our study makes a potential contribution to the mushroom cultivation and processing industry to achieve an improvement in sensory quality.